Novel multi-epitope protein containing conserved epitopes from different Leishmania species as potential vaccine candidate: Integrated immunoinformatics and molecular dynamics approach. (December 2019) - Ropón-Palacios, Georcki; Chenet-Zuta, Manuel E.; Otazu, Kewin; Olivos-Ramirez, Gustavo E.; Camps, Ihosvany
Graphical abstract: Highlights: Four epitopes were found to be conserved in the Leishmania species used ( L. braziliensis, L. mexicana, L. panamensis and L. guyanensis ). The quality of the 3D structure was analyzed using reference tests; obtaining a model with high-resolution (1.452 Å). The high structural stability of the model was proved using molecular dynamics. Protein-protein docking between the model and TLR T-cell receptor shown strong H-bond and hydrophobic interaction indicating a high affinity. Abstract: Leishmaniosis, caused by intracellular parasites of the genus Leishmania, has become a serious public health problem around the world, and for which there are currently extensive limitations. In this work, a theoretical model was proposed for the development of a multi-epitope vaccine. The protein GP63 of the parasite was selected for epitopes prediction, due to its important biological role for the infection process and abundance. IEDB tools were used to determine epitopes B and T in Leishmania braziliensis ; besides, other conserved epitopes in three species were selected. To improve immunogenicity, 50S ribosomal protein L7 / L12 (ID: P9WHE3) was used as a domain of adjuvant in the assembly process. The folding arrangement of the vaccine was obtained through homologous modeling multi-template with MODELLER v9.21, and a Ramachandran plot analysis was done. Furthermore, physicochemical properties were described with the ProtParam tool and secondary structure prediction combining GOR-IV and SOPMA tools. Finally, a molecular dynamics simulation (50 ns) was performed to establish flexibility and conformational changes. The analysis of the results indicates high conservancy in the epitopes predicted among the four species. Moreover, Ramachandran plot, physicochemical parameters, and secondary structure prediction suggest a stable conformation of the vaccine, after a minimum conformational change that was evaluated with the free energy landscape. The conformational change does not drive any substantial change for epitope exposition on the surface. The vaccine proposed could be tested experimentally to guide new approaches in the development of pan-vaccines; vaccines with regions conserved in multiple species.